Rola Unii Europejskiej w zwalczaniu totalitaryzmu i autorytaryzmu na świecie – ambicje i przeszkody - Kornobis-Romanowska, Dagmara (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The European Union is a community of member states based on law and with axiological guarantees at its foundation. The Union is an legal entity whose goal is to protect its own values and interests and to protect its citizens, not only in its internal activities, but also in its external relations. These are activities for the benefit of the international community that protect against divisions, splits, radicalism, and the spread of autocratic and totalitarian ideas in Europe and the world. The rules are laid down in the Treaty on European Union and its provisions — art. 2 TEU, art. 3(5) and 21 (2) TEU. The main research question of the presented text is how the above legal obligations are fulfilled by the Union in times of current political and legal crises? What are or should be the consequences from the EU towards aggressors? What about Russia invading Ukraine and committing international crimes? Given that this situation is unprecedented, the Union, as a member of the international community, is taking several actions beyond the competences conferred directly on it in the Treaties. This is met with external and internal criticism in the EU, giving rise to numerous legal obstacles, including formal ones. In these conditions, the Union refers to the actions of Mem- ber States, based on the a priori assumption of compliance with the norms of international law. These actions are the result of the Union’s ambition to turn the “dynamics of Ukraine” into an opportunity to develop new standards in responding to crisis situations and dealing with impunity of aggression anywhere in the world. However, these ambitions have a chance of success only if they are implemented in the spirit of respect for the law and common values in the international community.
Keywords: Unia Europejska; totalitaryzm; agresja; zbrodnia międzynarodowa; sądownictwo międzynarodowe; Ukraina